Outcome of liver disease associated with alpha 1 antitrypsin deficiency (PiZ). Implications for genetic counselling and antenatal diagnosis. Issue 11 (November 1983) - Psacharopoulos, H T; Mowat, A P; Cook, P J; Carlile, P A; Portmann, B; Rodeck, C H
Abstract : We reviewed the hepatic features in 136 children with alpha 1 antitrypsin deficiency (PiZ). Eighty two were studied prospectively, 74 of whom had chronic liver disease. Sixty seven children with liver disease presented in the first four months of life, four were older infants and children with chronic liver disease, 10 (three with liver disease) were identified in studies of the family of these propositi, and one was identified when she had liver disease associated with infectious mononucleosis. By 17 years of age 20 of these 74 children with chronic liver disease had died, 20 had established cirrhosis, 19 had persisting liver disease, and only 15 had made a complete, clinical and biochemical recovery. The outcome of liver disease was similar in a further 39 previously unreported PiZ infants and children with liver disease who were not prospectively studied. Because liver disease affects only a proportion of infants with PiZ phenotype and because the severity of their liver disease is so variable, we have analysed the outcome of liver disease in 27 observed families and in 20 previously reported families with more than one child with PiZ. In 34 families the outcome of liver disease was similar in the two children. From an analysis of the families with a severely affected child, we conclude that if the first PiZ child of PiZ heterozygote parents has unresolved liver disease, there is a 78% chance that a second PiZ child will have similar liver disease. After careful counselling, fetoscopy, fetal blood sampling, and protease inhibitor phenotyping, possible termination of pregnancy should be carefully considered in these families.